The Influence of Using Digital Comic Strips on the Vocabulary Mastery of Eighth Graders at SMPN 6 Cilegon - Insam, Verosita; Syafrizal; Sadji Evenddy, Sutrisno (Papanda, 2025)
This study aims to examine the effectiveness of using digital comic strips to improve vocabulary mastery among eighth-grade students at SMPN 6 Cilegon. The problem addressed is the low vocabulary achievement caused by conventional teaching methods that are less engaging and lack contextual relevance. To address this, digital comics integrating visual and narrative elements were applied in classroom instruction. The research employed a quasi-experimental design with two groups: an experimental group and a control group, each consisting of 17 students. A vocabulary test was used as the research instrument, administered before and after the intervention. The results showed that students who learned with digital comic strips demonstrated better vocabulary retention, higher motivation, and more consistent learning outcomes. Difficult words were more easily understood when presented through visual and narrative contexts. The study concludes that digital comic strips are an effective and inclusive instructional medium for vocabulary learning in English as a Foreign Language (EFL) settings. It is recommended that this media be integrated into curriculum design to enhance language learning outcomes.